The Foresight Approach to Researching Innovative Activity in High-tech Businesses - Sibirskaya, Elena V.; Shestaeva, Katerina A.; Smelov, Pavel A.; Oveshnikova, Lyudmila V. (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
The current stage of Russia’s development has compelled its authorities, business community and researchers alike to show interest in Foresight research for solving complex problems. These problems include attempts to evaluate innovation that could have a strong impact on the country’s economy in the short and long term and on a macro-, meso- and micro level. This study analyses the use of foresight methods in public administration and the most dynamically developing sector of the economy, technology. It also proposes a foresight approach to researching innovation.